Assessing the status of e-learning during the pandemic (COVID-19) - a selected sample of undergraduate students at Ha'il University - Fadi Ghawanmeh (Umm Al-Qura University, 2022)
The study aimed to reveal the reality of using e- learning in light of the Corona pandemic (Covid 19) from the point of view of Hail University students and the challenges they face. The study sample consisted of (1518) male and female students, they were selected by random sampling method, the quantitative descriptive approach was used, the applied study questionnaire consist of (38) items distributed on (3) areas, and an open question on the challenges facing university students Hail. The finding of the study showed that Corona pandemic (Covid 19), university infrastructure and direction towards e learning played a significant role. The study showed insignificance difference in gender and house address. However, the type of study stream appeared to play a significance role particularly with humanity stream students. The findings also revealed that the most significant challenges confronting Hail University students in the reality of using distance learning in the aftermath of the Corona (Covid 19) pandemic were "the students' sense of social isolation and the difficult psychological state of the difficulty of academic courses during lectures, particularly among students of scientific disciplines." In light of the study's findings, the researcher proposes that technology be used in teaching on an ongoing basis, as well as training faculty members on how to use technology and programs of distant learning platforms.